THE INFLUENCE OF NATIVE LANGUAGE ON YOUNG INDONESIAN LEARNERS’ ABILITY TO PRONOUNCE ENGLISH SHORT VOWELS - Ni Luh Desy Suari Dewi; I Gede Neil Prajamukti Wardhana; Yohanes Octovianus L. Awololon (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
This study examines the influence of native language on the ability of young Indonesian learners to pronounce English short vowels. Focusing on kindergarten-level students in Badung, Bali, the research explores difficulties in producing English vowel sounds absent in the Indonesian vowel system. Through observation and analysis of students’ pronunciation recordings of consonant-vowel-consonant (CVC) words, the findings reveal that vowel sounds such as /æ/, /ʌ/, and /ɒ/ are often substituted with more familiar vowels from the Indonesian language, such as /e/ and /o/. These mispronunciations are attributed to the limited vowel system of Indonesian, which consists of only five primary vowels. The results support the theory of first language (L1) interference, which posits that differences in phonological structures between the native and target languages pose challenges in language learning. This study highlights the importance of increased exposure to English pronunciation and phonetic practice to enhance learners' pronunciation skills.